Development of Christian Character Education Learning Design - Jhoni Siang; Budi Harwanto; Subaedah Luma (JTP - Jurnal Teknologi Pendidikan, 2026)
Despite the growing emphasis on character education, many Christian schools still lack a systematic and contextual learning design that effectively integrates Gospel values into classroom practice. This study addresses the problem of how to design a Christian character education learning model that is pedagogically structured, value-based, and applicable in real learning situations. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis of learning needs, design of instructional components, development of learning prototypes, implementation in an eighth-grade classroom, and evaluation through expert validation and user testing. The research involved 30 eighth-grade students and two Christian Religious Education teachers at SMPN 11 Tidore Kepulauan. The results indicate that the developed learning design achieved high validity scores from content experts (4.6), language experts (4.2), and media experts (4.1), and was positively received by users (4.4). In addition, observational data showed that 87% of students demonstrated improved understanding and application of Christian character values, particularly love and honesty. The novelty of this study lies in the integration of Gospel-based character values with an ADDIE-based instructional design that emphasizes active learning, reflection, and real-life application. The study concludes that the proposed learning design is feasible and effective for strengthening Christian character education and has practical implications for teachers in designing